1770 "You'Ll Be Fine" (Please Don'T Die!); The Experience of Uncertainty Among Gp Trainees. (October 2012) - Loftus, A; Keaveney, L; O'Neill, M
Abstract : Background and Aims: Uncertainty is at the heart of clinical practice. The learning curve leading from apprentice to expert brings us into contact with uncertainty on a daily basis yet there is relatively little emphasis on it in medical training. This project aimed to explore GP trainees' experience of uncertainty, its impact, and the skills required to counter it. Methods: An eight question survey was distributed to trainees on the Western Training Programme in General Practice exploring their decisiveness, their experience of uncertainty, and the resources they employed to deal with it. Results were analysed with Excel. Results: 45 questionnaires were returned (78% response rate). In terms of combating uncertainty, experience and knowledge of "red flags" ranked highest. Clinical knowledge and experience had the biggest impact on decision making, with fear of making a mistake more pronounced among trainees reporting higher degrees of uncertainty (94% said it inflluenced their decisions compared to 58% of the occasionally uncertain). Patients' anxieties and expectations impacted to a lesser extent (74%). Conclusion: How often trainees experience uncertainty may lessen with advancing clinical knowledge and experience. Support from senior colleagues is important, as is fear of making mistakes. Building personal resilience (emotional support, good lifestyle), and developing self-awareness didn't rank as highly in terms of what trainees found helpful in dealing with uncertainty; perhaps a reflection of a lack of emphasis on these in general in medical training and something that could be explored as a basis for student education in coping with uncertainty.